The Measuring System for Evaluation of Parameters of Integrated Mach-Zehnder Modulator - Svarny, Jiri (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with some issues linked to practical application of the analog intensity electro-optic modulator of Mach-Zehnder type. An accurate adjustment and long-term stabilization of optimal operating point of the modulator belongs to the most severe problems linked to implementation of the appliance like this. The paper describes functionality of Mach-Zehnder modulator, highlights some of the problems the designer is faced to and presents the methodology that has been used to measure parameters of the modulator that are not specified in the manufacturer data-sheet and might be helpful to solve the problem.